A proteostasis network safeguards the chloroplast proteome. Issue 2 (5th August 2022) - Llamas, Ernesto; Pulido, Pablo
Abstract: Several protein homeostasis (proteostasis) pathways safeguard the integrity of thousands of proteins that localize in plant chloroplasts, the indispensable organelles that perform photosynthesis, produce metabolites, and sense environmental stimuli. In this review, we discuss the latest efforts directed to define the molecular process by which proteins are imported and sorted into the chloroplast. Moreover, we describe the recently elucidated protein folding and degradation pathways that modulate the levels and activities of chloroplast proteins. We also discuss the links between the accumulation of misfolded proteins and the activation of signalling pathways that cope with folding stress within the organelle. Finally, we propose new research directions that would help to elucidate novel molecular mechanisms to maintain chloroplast proteostasis.